Stability and takeoff ground roll issues of hybrid buoyant aircraft - UlHaque, Anwar; Asrar, Waqar; Omar, Ashraf Ali; Sulaeman, Erwin; Ali, JS Mohamed (Trans Tech Publications Ltd., Switzerland, 2014)
Abstract. In the field of aviation, it is well known that a vehicle’s stability and takeoff flight segment are critical issues for a flight vehicle design. These problems become more critical for a hybrid buoyant aircraft which is concealed as an airship with huge volume of hull as compared with fuselage of a conventional aircraft. In the present work, these issues are discussed for a case of generic model of hybrid airship and of a prototype model of a hybrid aircraft. Special emphasis is given for future sizing of empennages of IWHA-14, a hybrid buoyant aircraft concept proposed for Malaysian inter-island transportation. Effect of gondola position on rotation angle for takeoff ground roll was analyzed and it was found that such configurations can meet the laid down requirement of minimum roll angle.